Rancang Bangun Alat Kardiografi Berbasis Impedansi Listrik (Electrical Impedance Cardiography): Fajar Timur, Endarko Endarko - Fajar Timur Fajar Timur; Endarko Endarko (Jurnal Fisika dan Aplikasinya, 2020)
Electrocardiography is a process or method to observe and record the activity of the heart by using a graph of electrical voltage versus time. A standard plan to achieve this is by measuring the bioelectric potential or bioimpedance of the heart organ. In this research, an electrical impedance cardiography device will be designed and tested. The process is carried out by using four electrodes that are attached at the neck and the diaphragm level of the body, an electric current with a specific value and frequency, then injected on a pair of electrodes, and the voltage will be measured on other pair of electrodes. The device testing process is carried out on subjects in good health and having no medical abnormality in a sitting and upright position. Impedance data will be measured and recorded at each time; the data that has been obtained will then be processed to determine the impedance graph Z and the first derivative of Z (dZ/dt). The number of heartbeats will also be calculated each time with another method, which is by using a stopwatch to compare the validity of the heart rate readings from the impedance cardiography device. The result demonstrated that the electrical impedance cardiography device that has been made could be used to illustrate heart rate graphs as a result of cardiovascular activity.